Composição e influência da heterogeneidade ambiental na diversidade de anfíbios em fragmentos de restinga no Delta do Parnaíba, nordeste do Brasil - Araújo, Kássio de Castro (2017)
For more than two centuries, knowing which species, where they are and why they are in certain places is something that arouses curiosity in scientists around the world and it is fundamental to the understanding of the complexity of biological diversity. The environment structure has a great importance for species richness, in which the larger the complexity of the environment is the larger is the species richness. Therefore, the present study aimed to investigate the composition and the influence of habitat heterogeneity and environmental variables on the diversity of amphibians in fragments of resting in the Parnaíba River Delta. Then we selected six collection points on the two largest islands in the Delta. The habitat heterogeneity was obtained from the environmental descriptors such as duration, size and maximum depth of the water body, percentage of vegetation cover on the surface of the water body, types of vegetation inside the body of water, types of marginal vegetation and the profile of the banks. We tested the null hypothesis of absence of association between habitat heterogeneity and environment variables with species diversity. The amphibian diversity was measured using the Shannon-Wiener diversity index and its relation with habitat heterogeneity and environmental variables: rainfall, humidity, temperature and photoperiod was obtained from the Linear Regression. It was recorded the total of 22 species labeled in six families, with eight new records to Ilha das Canárias and other one to Ilha Grande de Santa Isabel. It was checked that the habitat heterogeneity of the Parnaíba River Delta influence the amphibians’ diversity from region significantly, as well as humidity, whereas temperature exhibited low influence and rainfall and photoperiod showed no significant relation with amphibian diversity.